More frequent diagnosis of acute myocardial infarction among Navajo Indians. - Klain, M (1988)
In an earlier study, we failed to confirm a clinical impression that the incidence of acute myocardial infarction (AMI) was increasing in Navajo men. Extending our data collection an additional three years, through 1986, we observed that the attack rate in men more than doubled and there was a gradual increase among women. Most Navajos who sustain AMI are hypertensive (51 per cent), diabetic (50 per cent) or both (31 per cent), but few smoke cigarettes.